Pengenalan Digital Dalam Membentuk Milenial Kreatif Untuk Menghadapi Era Society 5.0 Di Kabupaten Enrekang - Endang, Andi Hutami; Pramita, Andi Jumiati; Syahruddin, Ahmad Dzulfajri; Syafaat, Muhammad; Ismaya, Ismaya (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
prioritizing the millennial generation who are creative with digital in the era of society 5.0 is a must for Engkreng District. This is because it produces a lot of digital transformation, especially in the field of Education which can create opportunities for more creative and highly competitive human resources. Introduction and training on the proto.io and google site form platforms, with data collection methods as follows: the preparation stage and the implementation stage. During the activity the lecture and practice methods were accompanied by demonstrations where participants were provided with modules for practicum. The background to this collaboration is the need to provide a basis for digitization and understand the relevance of technology in the era of society 5.0. With this activity, the organizers realize how important technology is in this era. Participants also realized that currently there are many facilities on the internet that can be used to support participants' creativit. memprioritaskan generasi milenial yang kreatif dengan digital di era society 5.0 adalah suatu keharus oleh Kabuoaten Engkreng. Hal ini karena menghasilkan banyak transformasi digital terutama di bidang Pendidikan yang dapat menciptakan peluang untuk sumber daya manusia yang lebih kreatif dan daya saing tinggi. Kegiatan pengenalan dan pelatihan plat form proto.io dan google site, dengan metode pengumpulan data sebagai berikut tahap persiapan dan tahap pelaksanaan. Selama kegiatan berlangsung metode ceramah dan praktek yang disertai dengan demonstrasi dimana peserta dibekali modul untuk praktikum. Latar belakang kolaborasi ini adalah kebutuhan untuk memberikan dasar digitalisasi dan memahami relevansi teknologi di era society 5.0. Dengan kegiatan ini, penyelenggara menyadari betapa pentingnya teknologi di zaman ini. Peserta juga menyadari bahwa saat ini ada banyak fasilitas di internet yang dapat digunakan untuk mendukung kreatifitas peserta.